Factor Analysis of Teaching Readiness Among PKK Students Specializing in Culinary Arts - Ilhami Pebi Widyawati; Juliana Siregar; Elida Elida; Cici Andriani (Jurnal Pendidikan Tata Boga dan Teknologi, 2025)
Teaching readiness among vocational education students is a critical issue in higher education, particularly for those in the Culinary Arts concentration of the Family Welfare Education (PKK) program. One of the key factors influencing students’ readiness to become professional teachers is Field Teaching Experience (PLK), which serves to bridge theoretical learning and classroom practice. This study aimed to analyze the effect of PLK on the teaching readiness of PKK Culinary Arts students. Using a quantitative descriptive approach and simple linear regression analysis, data were collected from 50 students selected by random sampling from a population of 100 at Universitas Negeri Padang. A four-point Likert-scale questionnaire was used, with validity tested through Pearson Product Moment and reliability confirmed using Cronbach’s Alpha (α = 0.871). The findings showed that PLK had a significant positive effect on teaching readiness, with a regression coefficient of 1.057, t-value of 5.131, and significance level of 0.000 (p < 0.05). The coefficient of determination (R²) was 0.354, indicating that PLK accounts for 35.4% of the variance in teaching readiness. These results reinforce the importance of structured teaching experiences in preparing vocational education students to become effective educators and suggest the need for continuous improvement in the implementation of PLK programs.